Strategies for Instructional Supervision in Secondary Schools under the Office of the Secondary of the Secondary Educational Service Area 7 - Sriyoo, Papawee; Thanompongchart, Phasphan; Sudrung, Jurairat (An Online Journal of Education, 2021)
The research had two objectives: 1) to study the current and desirable conditions of instructional supervision in secondary schools under the Secondary Educational Service Area Office 7, and 2) to propose strategies for instructional supervision in secondary schools under the Office of the Secondary Educational Service Area 7. The population was 44 secondary schools under the Secondary Educational Service Area Office 7. There were 264 respondents which included the deputy directors of academic affairs and the head teachers of five learning subject groups from each school. The data analysis included frequency, percentage, mean, and standard deviation calculations as well as Priority Needs Index (PNI) Modified and content analysis. The results showed that the overall current conditions of instructional supervision were at a high level (M = 3.95). The overall desirable supervisory conditions were at the highest level (M = 4.50). The PNI of overall instructional supervision was 0.139. Strategies for instructional supervision consisted of three main strategies, six sub-strategies, and 12 methods of implementation. Strategy one is to build an understanding of the supervision principles. Strategy two is to promote a systematic operation of instructional supervision. Strategy three is to include the instructional supervision programs in the schools’ annual action plan.